Effects of Cu(Ⅱ) stress on embryonic development, oxidative stress response, cholinergic system and energy metabolism in the Sepiella maindroni - Qilong Huang; Jiawen Yu; Ruibing Peng; Maowang Jiang; Qingxi Han; Xiamin Jiang (Ecotoxicology and Environmental Safety)
In order to investigate the causes of population degradation and resource decline, this thesis investigated the ecotoxicological effects of heavy metal Cu(Ⅱ) on the embryonic development of Sepiella maindroni. Results indicate significant effects of Cu(Ⅱ) concentrations on the developmental toxicity, teratogenicity, and lethality of S. maindroni embryos. Different concentrations of Cu(Ⅱ) caused varying degrees of malformations in embryos, altered developmental rates, reduced hatchability and hatchling quality, and increased malformation and mortality of hatchlings. At the same time, Cu(Ⅱ) exposure led to an increase in the content of the lipid peroxidation product malondialdehyde (MDA) and a significant decrease in the activity of antioxidant enzymes (superoxide dismutase [SOD], catalase [CAT]), energy-metabolizing enzymes (adenylate kinase [AK]), and cholinergic-related enzymes (acetylcholinesterase [AChE], choline acetyltransferase [ChAT]). In conclusion, when the concentration of Cu(Ⅱ) in the environment is ≥ 0.01 mg/L, it causes significant lethality toxicity, developmental toxicity and teratogenicity in S. maindroni embryos. These effects are likely related to Cu(Ⅱ)-induced stress impacting the antioxidant capacity, energy metabolism, and cholinergic system. Ultimately, these toxic effects may lead to population degradation and resource decline in fishery organisms by affecting the early replenishment process of fisheries.